Kemampuan Komunikasi Matematis Ditinjau dari Tipe Kepribadian Extrovert dan Introvert - Khaeriyah, Annisa Nur; Firmansyah, Dani (Radian Journal: Research and Review in Mathematics Education, 2023)
The purpose of this research is to determine the mathematical communication abilities of junior high school students based on extrovert and introvert personality types. This research employs a qualitative descriptive research method. The researchers selected students from SMP Negeri 5 West Karawang who have received material on relations and functions as the population for this study. The data collected by the researchers consist of written test instruments, questionnaires, and interviews. The data analysis process in this research includes collection, reduction, presentation, and drawing conclusions. The findings reveal differences in mathematical communication abilities between students with extroverted and introverted personalities. Extrovert students, characterized by high self-confidence, tend to show carelessness and incompleteness in documenting the steps in solving problems. Meanwhile, introvert students, due to lower confidence in their understanding, tend to be more careful and complete in expressing ideas and outlining steps to solve a problem. Suggestions that the researchers can convey include the hope for further research to be more mature in preparing studies, in creating or choosing essay tests, it is recommended to use language that is easy for students to understand to avoid confusion. Additionally, further research is needed focusing on improving the communication skills of class VIII junior high school students.